2008
DOI: 10.1088/0957-4484/19/49/495203
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic admittance of carbon nanotube-based molecular electronic devices and their equivalent electric circuit

Abstract: We use first-principles quantum mechanics to simulate the transient electrical response through carbon nanotube-based conductors under time-dependent bias voltages. The dynamic admittance and time-dependent charge distribution are reported and analyzed. We find that the electrical response of these two-terminal molecular devices can be mapped onto an equivalent classical electric circuit and that the switching time of these end-on carbon nanotube devices is only a few femtoseconds. This result is confirmed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
61
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 38 publications
2
61
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10] As a formally rigorous and numerically tractable approach, TDDFT promises real-time simulations on ultrafast electron transport through realistic electronic devices or structures. In early attempts, finite source-device-drain systems were treated by the conventional TDDFT for isolated systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8][9][10] As a formally rigorous and numerically tractable approach, TDDFT promises real-time simulations on ultrafast electron transport through realistic electronic devices or structures. In early attempts, finite source-device-drain systems were treated by the conventional TDDFT for isolated systems.…”
Section: Introductionmentioning
confidence: 99%
“…6 One of recent applications of the TDDFT-NEGF-EOM method was a simulation on the ultrafast transient current through a carbon nanotube based electronic device. It was found that the dynamic electronic response of the device can be mapped onto an equivalent classical electric circuit, 7,16 which would be useful for future design of functional devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Do conventional organic molecules behave as classical capacitors or inductors, or does their ac response depend on frequency and chemistry in a non-trivial way? This question was already addressed by Fu and Dudley in the 1990s for the model system of a resonant tunneling diode [14], and recently, several groups presented DFT based calculations of ac conductances for realistic molecular junctions [15,16,17,18,19].…”
mentioning
confidence: 99%
“…This is attributed to the fact that the kinetic inductance increases with the dwell time of electrons, which is due to the inertia of the electrons. 6 Investigations of the effect of contact between a pristine metallic CNT and metallic electrodes on the AC transport properties [7][8][9] have shown that the sub-terahertz frequency susceptance changes from an inductive response to a capacitive response with decreasing DC conductance. 8,9 This indicates that there is a correlation between the DC conductance and the subterahertz frequency susceptance.…”
mentioning
confidence: 99%